2016
DOI: 10.1055/s-0036-1592365
|View full text |Cite
|
Sign up to set email alerts
|

Bone Quality—Beyond Bone Mineral Density

Abstract: Both bone mass and quality are responsible for bone strength. Whereas bone mass is measured with bone mineral density, quantification of bone quality is more complex and involves bone architecture, texture, and mechanical parameters. Over the last decade, significant progress has been made in developing technologies to measure bone quality. These include novel low-cost modalities such as trabecular bone score measured on dual-energy X-ray absorptiometry images and quantitative ultrasound as well as more advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…In these and other studies, texture heterogeneity was described to be associated with therapy response and clinical outcome [ 35 ]. Besides MRI, the use of texture analysis was investigated on using mammography and in CT in the past to analyze its capability to contribute to computer-aided cancer diagnosis or bone quality measurements [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these and other studies, texture heterogeneity was described to be associated with therapy response and clinical outcome [ 35 ]. Besides MRI, the use of texture analysis was investigated on using mammography and in CT in the past to analyze its capability to contribute to computer-aided cancer diagnosis or bone quality measurements [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These texture parameters have been used for trabecular bone microstructure analysis in computed tomography (CT) scans and can similarly be applied on MR-based PDFF maps [ 21 ]. Additionally, certain texture features were shown to be of diagnostic help in identifying soft tissue malignancies from mammograms or fracture risk in CT [ 23 , 24 ]. With that said, the methodic deduction of the concept of using texture parameters to attain a diagnostic gain and subsequent transfer to MRI as radiation-free modality is a logical step and of high clinical significance with implementation in risk stratification for potential fractures or tumor relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these clinically relevant results, it should be kept in mind that the participants were menopausal women who were not receiving pharmacological treatments and who were at risk of osteoporosis-some of the women already had osteopenia. The bone compartment is quantified through the BMD, which informs the amount of bone that exists after the growth period is complete [9]. However, a disadvantage of the method used to assess the bone mass is that it is not significantly sensitive to predict fractures [39].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the risk of fracture can be calculated using the Fracture Risk Assessment Tool (FRAX ® ), a validated tool created by the WHO that estimates the 10-year risk of developing an osteoporotic fracture [8]. Finally, to quantify the bone mineral density (BMD), defined as the amount of bone that exists once the growth period is complete [9], there are several techniques, but, with no doubt, the most commonly used is dual-energy X-ray absorptiometry (iDXA). This is a non-invasive technique which is fast to perform with low amounts of radiation and with very a high accuracy and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…This information is obtained from second-order features which can be extracted from the gray-level co-occurrence matrix (GLCM) as described by Haralick et al (25). Texture features have previously been applied in different biomedical imaging modalities, e.g., for computed tomography (CT)-based analysis of bone microstructure, CTbased fracture risk assessment, and diagnostic support in mammography (26)(27)(28), in multi-modal oncologic imaging analysis (29)(30)(31) as well as for MRI-based computer-aided diagnosis and classification of vertebral compression fractures (32,33). In a recent preliminary study, CSE-MRI-based texture analysis demonstrated an increased vertebral bone marrow heterogeneity after menopause and the second-order features contrast and dissimilarity were shown to differentiate postfrom premenopausal equally well as PDFF (24).…”
Section: Introductionmentioning
confidence: 99%